2017
DOI: 10.1007/s10802-016-0234-9
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Coregulation in Mother-Child Dyads: A Dynamic Systems Analysis of Children with and without Autism Spectrum Disorder

Abstract: Few studies have investigated patterns of emotion coregulation in families of children with Autism Spectrum Disorder (ASD) or contrasted the ways in which their emotion coregulation patterns differ from families of typically developing (TD) children. To address this gap, we used a dynamic systems approach to compare flexible structure and emotional content of coregulation between mothers and children (3-7 years) with ASD (n = 47) and TD children (n = 26). Mother-child play interactions in the home were videota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 54 publications
2
22
0
Order By: Relevance
“…The study confirmed what was already emerging in the relevant literature ( Feldman and Klein, 2003 ; Hirschler-Guttenberg et al, 2015 ), namely, that parents of children with ASDs used the same parental disciplinary style of parents of TD children, and that a more supportive parental disciplinary style was associated with more child self-regulated compliance. According to a 2017 study in an ASD group, mother–child dyadic interactions were more engaged in mismatched emotion-engagement states and children spent more time exclusively with objects than the dyads in the TD group ( Guo et al, 2017 ). Another recent study used a narrative methodology to study fathers’ stories of play interaction with their children with ASD aged between 5 and 12 years old.…”
Section: Introductionmentioning
confidence: 99%
“…The study confirmed what was already emerging in the relevant literature ( Feldman and Klein, 2003 ; Hirschler-Guttenberg et al, 2015 ), namely, that parents of children with ASDs used the same parental disciplinary style of parents of TD children, and that a more supportive parental disciplinary style was associated with more child self-regulated compliance. According to a 2017 study in an ASD group, mother–child dyadic interactions were more engaged in mismatched emotion-engagement states and children spent more time exclusively with objects than the dyads in the TD group ( Guo et al, 2017 ). Another recent study used a narrative methodology to study fathers’ stories of play interaction with their children with ASD aged between 5 and 12 years old.…”
Section: Introductionmentioning
confidence: 99%
“…The SSG has recently been used to examine emotion coregulation in mothers and children with ASD (Guo et al 2017); more commonly, it has been used to examine dyadic emotion processes and maladaptive behaviors in high-risk children and children with behavior problems. For example, Hollenstein and colleagues (2004) observed parents and high-risk kindergarteners during various structured activities and examined the flexibility of interactions.…”
Section: State Space Gridmentioning
confidence: 99%
“…The conceptualizations of parentchild dyadic synchrony encompass an array of interactive behaviors, such as responsiveness, reciprocity and shared emotion evaluated during face-to-face interactions (16). The development of children's emotional regulation occurs through repeated emotional experiences with parents, and shared emotion, as an aspect of dyadic synchrony that lays the foundation for the development of subsequent self-regulation, may differ between children with ASD and typically developing children (17)(18)(19). Although parent-child dyadic synchrony plays an important role in children's development, studies have only recently focused on it and regarded it as an important indicator of parent-child relationship quality (20), and few researchers have suggested that parent-child synchrony should be considered a factor in the efficacy of interventions for children with ASD.…”
Section: Introductionmentioning
confidence: 99%